Australian Validation of the Hierarchical Personality Inventory for Children (HiPIC). Issue 2 (16th May 2014) - Hopkinson, Laura; Watt, Dianne; Roodenburg, John
Abstract : The Hierarchical Personality Inventory for Children (HiPIC) is a developmentally appropriate parent-report measure of the Five Factor Model (FFM) that has been validated in several European languages but only recently in English. The English translation of the HiPIC was evaluated in an Australian context. Parent-rated HiPIC scores were obtained for 202 children (aged 5–14 years) via an online survey. Exploratory factor analysis indicated five factors that appeared reasonably congruent with the original Flemish HiPIC structure, though with some apparent differences particularly in regard to the Extraversion and Benevolence facets. A Procrustes targeted rotation was used to evaluate the congruence with the original Flemish structure. This indicated encouragingly high congruences for the overall model (.97), as well as high facet and factor congruence (.92–.99). These findings can be taken to reflect the robust nature of the HiPIC model, validating the instrument and more specifically confirming its applicability for use in practice and research investigating children's development and wellbeing in Australia.